THE EFFECTS OF THE “KIDS ULTRA BENZ 10” PROGRAM ON PROMOTING HEALTH LITERACY AND DIETARY BEHAVIORS AMONG GRADE 4–6 PRIMARY SCHOOL STUDENTS WITH OVERWEIGHT IN SISAKET PROVINCE - ภารประดิษฐ์ พนิดา; ธรรมสาร กฤติยาณี (Primary Health Care Journal (Northeastern Edition), 2026)
Overweight and obesity among school-aged children are significant public health issues leading to non-communicable diseases (NCDs). Enhancing health literacy and dietary behaviors is crucial for preventing NCDs. This quasi-experimental research aimed to examine the effects of the “KIDS ULTRA BENZ 10” program on promoting health literacy and dietary behaviors among overweight grade 4–6 students in Sisaket Province. The sample comprised 82 students classified as overweight to obese, equally divided into an experimental and a control group (n = 41 each). The experimental group participated in the 10-week program, while the control group maintained their usual lifestyle. Data were collected using questionnaires and analyzed using descriptive statistics, independent t-test, paired t-test, chi-square test, and logistic regression. Results revealed that, post-intervention, the experimental group had significantly higher mean scores in all six components of health literacy and improved dietary behaviors compared to the baseline (p-value < 0.05). Conversely, the control group showed no significant differences. In conclusion, the program effectively enhanced health literacy and modified dietary behaviors among overweight students. Relevant authorities should integrate health literacy promotion guidelines emphasizing active learning and digital technology into national school policies to establish an effective mechanism for addressing childhood overweight conditions.